Hubungan Tingkat Pengetahuan Penggunaan Lensa Kontak Pada Pelajar Sekolah Menengah Atas terhadap Risiko Ulkus Kornea di Bandar Lampung - Ardella, Karina Belinda; Himayani, Rani; Utami, Nurul (Medula, 2023)
Contact lenses are visual aids that can be used to correct refractive errors and for cosmetic purposes. Knowledge of contact lenses usage influence contact lens wearing behavior. Corneal ulcer can be caused by improper use of contact lenses. The objective of this study is to determine the correlation between knowledge level of contact lenses usage with the risk of corneal ulcer among high school students in Bandar Lampung. This quantitative analytic study with a cross-sectional design was conducted in December 2020 - February 2021. Research respondents consisted of 54 high school students in Bandar Lampung who match the criteria and were selected randomly. The research instrument was a questionnaire to assess knowledge of contact lenses usage and symptoms that accompany contact lens usage. Data were analyzed by Fisher test. In this study, as many as 47 respondents (87.0%) were female. There are 32 respondents (59.3%) who use contact lenses to correct eye refractive disorders. As many as 50 respondents (92.6%) have good knowledge and 4 respondents (7.4%) have sufficient knowledge. Respondents with red eyes and decreased visual acuity are 8 respondents (16,7%). Respondents who are at risk of corneal ulcer are 3 respondents (5.6%). In the analysis of the correlation between knowledge level of contact lenses usage and the risk of corneal ulcers, p value = 1,000. In this study, knowledge level of contact lenses usage has no correlation with the risk of corneal ulcers among high school students in Bandar Lampung.